Trends in stroke occurrence in rheumatoid arthritis: a retrospective cohort study from Western Norway, 1972 through 2020 - Alsing, Christian Lillebø; Igland, Jannicke; Nystad, Tone Wikene; Gjesdal, Clara Gram; Næss, Halvor; Tell, Grethe S.; Fevang, Bjørg-Tilde (Frontiers in Medicine, 2025)
ObjectivesTo investigate stroke occurrence in patients with rheumatoid arthritis (RA) diagnosed from 1972 through 2013 compared with the total population.MethodsWe included 1821 patients diagnosed with RA from 1972 through 2013 at Haukeland University Hospital in Norway. The patients were divided into three inception cohorts by time of RA diagnosis (1972–1998, 1999–2006, and 2007–2013), based on major changes in RA treatment. The total population of the same county was used as a comparison cohort. Both cohorts were followed from 1972 through 2020. Annual change in stroke event rates were calculated by Poisson regression with adjustment for age and sex. Hazard ratios were estimated by Cox regression with adjustment for age, sex, smoking, BMI, diabetes and serological status. Standardized event ratios (SER) were estimated by Poisson regression as a measure of excess stroke events in patients with RA compared with the total population.ResultsIn total 156, 70, and 31 stroke events occurred in the first, middle, and last inception cohorts during, respectively, 17,110, 9,561, and 4,098 person-years of observation. From 1999 to 2020 stroke event rates declined by 4.8% (95% CI 2.7–6.9) per year in the RA cohort and by 3.4% (95% CI 3.1–3.7) per year in the comparison cohort. There was a trend towards lower stroke risk across inception cohorts, with a statistically significant reduction only observed among women in the last cohort compared to the first cohort (hazard ratio 0.30, 95% CI 0.12–0.76). Despite this reduction, the last inception cohort had the highest excess of stroke events (SER 1.58, 95% CI 1.03–2.43), compared with the total population. However, this excess stroke occurrence was only observed in men with RA and not in women with RA.ConclusionDespite an overall decline in stroke occurrence over time, men with RA diagnosed after 2007 had a residual excess stroke occurrence compared to the total population. No excess stroke occurrence was observed in women with RA from the same time period. Our findings highlight the continued need of targeted stroke prevention in patients with RA, particularly for men.